Perlindungan Hak Asasi Manusia atas Hak Politik Kaum Disabilitas dalam Pemilihan Umum - Muslikhah, Umi (UIR Press, 2017)
Ratification of the Convention on the Rights of Persons with Disabilities is a form of recognition and affirmation by the state that the Tribe disability can feel the same rights as citizens of other in civil, cultural, economic, political and social issues and includes all the rights and obligations of the state for the People with Disability in order to create fairness and independence. Elections is a feature or a sign of democracy in a democratic country. The limitations inherent in the disability does not necessarily eliminate the acquisition and fulfillment of the rights of persons with disabilities as citizens. Acquisition and fulfillment of the rights of persons with disabilities should be supported by the availability of infrastructure (Accessibility) that allows them to channel their political rights in general elections.Keyword: Disability, Political Right, General Election.